Kualitas Pelayanan Administrasi Kependudukan Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tojo Una-Una - Moh. Rizky Taftazany; Suasa Suasa; Muh Nawawi (JURNAL ILMIAH RESEARCH STUDENT, 2024)
In general, this research aims to find out the quality of Population Administration Services at the Population and Civil Registration Service of Tojo Una-Una Regency. In writing, this research uses a descriptive research method, namely research carried out in certain rules that exist in real life which describe and explain systematically and accurately the situation of the Quality of Population Administration Services at the Population and Civil Registration Service of Tojo Una-Una Regency. The basis of the research used is qualitative research. The theory used in this research is the theory of Zeithaml, Parasuraman, Bery and friends which includes five indicators, namely Physical Appearance, Reliability, Responsiveness, Assurance, and Empathy. The results of the research show that the Quality of Population Administration Services at the Population and Civil Registration Service of Tojo Una-Una Regency can be concluded that of the 5 (five) aspects used, namely Tangibles, Reliability, Responsiveness, Assurance and Empathy, 3 (three) aspects have worked well. optimal, namely Tangibles, Reliability, and Responsiveness. Meanwhile, 2 (two) aspects that have not run optimally are Assurance and Empathy.